2002
DOI: 10.1002/neu.10136
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin in the developing stomatogastric system of the lobster, Homarus americanus

Abstract: We studied the development of the serotonergic modulation of the stomatogastric nervous system of the lobster, Homarus americanus. Although the stomatogastric ganglion (STG) is present early in embryonic development, serotonin immunoreactivity is not visible in the STG until the second larval stage. However, incubation of the STG with exogenous serotonin showed that a serotonin transporter is present in embryonic and early larval stages. Serotonin uptake was blocked by paroxetine and 0% Na(+) saline. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…We have recently shown that transporters for another biogenic amine, serotonin, exist in the STG before the ganglion is capable of actually synthesizing serotonin (Richards et al, 2003). TH is present in neurosecretory structures as early as E35 , so dopamine is probably present in the hemolymph in embryos and could be used as a "borrowed transmitter" by the STG before TH is present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that transporters for another biogenic amine, serotonin, exist in the STG before the ganglion is capable of actually synthesizing serotonin (Richards et al, 2003). TH is present in neurosecretory structures as early as E35 , so dopamine is probably present in the hemolymph in embryos and could be used as a "borrowed transmitter" by the STG before TH is present.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages of these species for studies of adult modulation, in these species it has not yet been possible to obtain embryos and larvae to study the early development of the STG. In contrast, studies of modulation of the adult STG in Homarus americanus and Homa-rus gammarus have lagged behind those in P. interruptus and C. borealis, but in H. americanus and H. gammarus developmental studies are feasible (Casasnovas and Meyrand, 1995), and it is possible to study the actions of neuromodulators as early as 50% of embryonic development (Le Feuvre et al, 1999;Richards et al, 1999Richards et al, ,2003Richards and Marder, 2000). Previous work has shown that some neuromodulators are already present early in embryonic development, whereas others appear only during larval times (Cournil et al, 1995;Fénelon et al, 1998Fénelon et al, ,1999Kilman et al, 1999;Li et al, 2002).…”
mentioning
confidence: 92%
“…The effects of a given neuromodulator on a specific pattern generator often vary somewhat among animals, but most studies have focused on mean responses, and have reported similarities in the direction of these effects across the animal population Kreissl et al, 1999;Mercier et al, 2003;Richards et al, 2003;Stevens et al, 2008;Stevens et al, 2009). While a number of factors could potentially underlie the quantitative variability in responses across animals, differences in response to a given modulator have most often been attributed to the 'state' of the system; this in turn is often reflected in the starting parameters of the pattern, notably cycle frequency (Dickinson et al, 2001;Fu et al, 2007;Medler and Hulme, 2009;Nadim et al, 2008;Nagy and Dickinson, 1983;Nusbaum and Marder, 1989b;Sargeant, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…glion (Beltz et al, 1984;Marder and Eisen, 1984;Flamm and Harris-Warrick, 1986a,b;Harris-Warrick and Flamm, 1987;Harris-Warrick, 1989, 1990;Johnson and Harris-Warrick, 1990;Kiehn and Harris-Warrick, 1992a,b;Meyrand et al, 1992;Johnson et al, 1993;Turrigiano and Marder, 1993;Harris-Warrick, 1994, 1995;Christie et al, 1995;Hempel et al, 1996;Ayali and HarrisWarrick, 1999;Kilman et al, 1999;Tierney et al, 1999;Peck et al, 2001;Birmingham et al, 2003;Richards et al, 2003). To date, we have localized two serotonin receptors to the STG: 5-HT 2␤Pan and 5-HT 1Pan (Baro and M. C. Clark, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 different substances modulate the pyloric circuit, with monoamines figuring prominently among them (HarrisWarrick et al, 1992a;Pulver et al, 2003;Richards et al, 2003). Monoamines can alter the strength of synaptic interactions between pyloric neurons and/or their intrinsic properties (HarrisWarrick et al, 1998).…”
Section: Introductionmentioning
confidence: 99%